Examining the influence of price and accessibility on willingness to shop at farmers’ markets among low-income eastern North Carolina women - McGuirt, Jared T. (2013)
OBJECTIVE: To examine the influence of farmers’ market pricing and accessibility on willingness to shop at farmers’ markets, among low-income women. DESIGN: Qualitative interviews using scenarios with quantitative assessment of willingness to shop at farmers’ market given certain pricing and accessibility scenarios. SETTING: Eastern North Carolina. PARTICIPANTS: Thirty seven low-income women of child-bearing age (18-44 years) receiving family planning services at the health department. PHENOMENON OF INTEREST: Willingness to shop at a farmers’ market. ANALYSIS: Fisher’s exact test was used to examine associations between willingness to shop at farmers’ markets by urban/rural residence, race, and employment status. Direct quotations relevant to participants' use of farmers' markets were extracted based upon a positive deviance framework. RESULTS: Participants were increasingly willing to shop at the farmers’ market when price savings increased and when the market was incrementally closer to their residence. Willingness was highest when there was at least a 20% price savings. Participants seemed to be influenced more by a visual representation of a greater quantity of produce received with the price savings rather than the quantitative representation of the money saved by the reduced price. CONCLUSIONS AND IMPLICATIONS: Future farmers’ market interventions should take into account these consumer level preferences.